WebNCL: a web-based presentation machine for multimedia documents - Melo, Erick Lazaro; Viel, Caio César; Teixeira, Cesar A. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Presentation machines for multimedia declarative languages especially the ones related with Interactive Digital TV (iDTV) and Internet Protocol TV (IPTV) are usually embedded in devices and strongly coupled with the platforms when native code and API for the device's platform are used. Since much of the complexity to implement presentation machines lies on presenting and controlling different types of media (video, audio, image, text), and given that most of the modern browsers natively support those requirements, it becomes interesting to implement presentation machines using Web technologies to reduce their coupling with platforms. In this paper we discuss the advantages of a presentation machine for declarative multimedia languages implemented on top of Web technologies. As a proof of concept we implemented the WebNCL, a lightweight NCL presentation machine based on the web technologies stack (HTML 5/ JavaScript/ CSS). By using WebNCL, NCL documents can be presented in any device that has a HTML5 compatible browser, such as tablets, smartphones, smart TVs and PCs.